Discourse analysis of environmental policy revisited: traditions, trends, perspectives. Issue 5 (3rd September 2019) - Leipold, Sina; Feindt, Peter H.; Winkel, Georg; Keller, Reiner
ABSTRACT: Since the mid-1990s, discourse analysis has become an increasingly established framework in environmental policy analysis. The field has diversified in terms of conceptual approaches, methods, topics, and geographies. This special issue revisits trends and traditions regarding theoretical and methodological approaches, 'old' and 'new' discourses, and our knowledge about discursive effects. We contextualize and discuss the twelve contributions to this special issue against the broader trajectory of the field over the past 25 years. Our analysis reveals an abundance of theoretical approaches with limited cross-fertilization, a plethora of rich case studies but few attempts at meta-analysis, and subtle accounts of discursive effects on discourse, policy and practice without an overarching framework. We suggest seven directions for the field's future evolution: a need for more comparative and multiple-case studies, theoretical cross-fertilization, pro-active integration of non-English-speaking research contexts, development of methodological capabilities to capture discursive developments across larger numbers of publics and policy arenas, a more explicit conceptualization of agency, power and materiality, a stronger collaboration with transdisciplinary approaches, and a reflexive engagement with the 'critical' ambition of discourse analysis.